Synthesis of solid electrolyte compatible with cathode materials based on double perovskites for solid oxide fuel cells - Кутербеков К. A.; Кабышев , А. М.; Бекмырза, К.; Кубенова , М.; Айдарбеков , Н.; Никонов, А. (BULLETIN OF THE L.N. GUMILYOV EURASIAN NATIONAL UNIVERSITY. PHYSICS. ASTRONOMY SERIES, 2022)
This paper studies the effect of small additives of transition metal oxides (sodopants) on the properties of the solid electrolyte GDC. Samples of dense ceramics of compositions Ce 0,9(1−x) Gd 0,1(1−x) M x O 2−∆ (x = 0,01, 0,03, 0,05; M = Co, Cu, Mn, Zn) have been synthesized by sintering compacts. The authors have carried out dilatometric studies of the initial powders and determined the optimal sintering temperature. It has been determined that sodopants improve the GDC sintering ability because during sintering they form a liquid phase, which increases the rate of interparticle diffusion. As part of the study there has been measured the conductivity of the synthesized samples. The article considers influence of sodopants on the phase composition of the samples.